2021
DOI: 10.1111/jog.14723
|View full text |Cite
|
Sign up to set email alerts
|

Lnc‐RNA LINC01279 induces endometriosis via targeting of HOXA10

Abstract: Aim To explore the regulatory role and molecular mechanism of lncRNA‐LINC01279 in endometriosis (EMs). Methods Between September 2018 and July 2019, 20 EMs patients and 20 healthy subjects were recruited to detect the expression of lncRNA‐LINC01279 in EMs and in normal endometrium via qRT‐PCR. Autograft was used to establish EMs models on Spraque–Dawley (SD) rats, which was followed by taking volume measurements of EMs endometrium and observing pathological changes in the morphology of EMs via hematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We found that either high or low expression of LINC01279 is correlated with a reduced OS rate in patients with LUAD. There is also evidence that upregulation of LINC01279 may be related to tumor invasion in gastric cancer [ 10 ]. Thus, it may represent a potential therapeutic target to prevent tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that either high or low expression of LINC01279 is correlated with a reduced OS rate in patients with LUAD. There is also evidence that upregulation of LINC01279 may be related to tumor invasion in gastric cancer [ 10 ]. Thus, it may represent a potential therapeutic target to prevent tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent works suggested that its function could be associated with the pathogenesis of endometriosis [ 8 , 9 ]. Interestingly, more recent studies indicated a correlation between LINC01279 expression and progression of gastric cancer [ 10 ], suggesting a possible function of this IncRNA in regulating tumor growth. However, whether it plays a role in other cancers is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Non coding RNAs have been reported to play key roles in musculoskeletal conditions [6][7][8]. LncRNAs are a noncoding RNA with a length of more than 200 nucleotides [9]. The abnormal expression or function of lncRNA is closely related to the occurrence of human diseases, including breast cancer [10], liver diseases [11] and many other major diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Many biomarkers have been proposed in the literature; however, none have been found, either alone or combined in a panel of markers, to yield sensitivity and specificity equivalent to laparoscopy [ 13–15 ]. In recent years, exosomes and their cargo [ 16 ], tissue concentrations of circular RNA [ 17 ], and long noncoding RNA [ 18 ] as well as circulating concentrations of microRNAs (miRNA) [ 19–21 ] have been documented in women with endometriosis compared with control populations and thus are thought to have potential value as candidate diagnostic markers of endometriosis [ 22 , 23 ]. Of these biomarkers, miRNA have received the greatest attention in the literature.…”
Section: Introductionmentioning
confidence: 99%